Experimental and numerical study on seismic behaviors of SRC column-RC slab joints in NPP - Dayang Wang; Qiang Liu; Yuanqi Song; Yong Zhu; Yongshan Zhang (Nuclear Engineering and Technology)
This paper presents an innovative design of a steel-reinforced concrete (SRC) column-reinforced concrete (RC) slab joint based on a concept of the strong column and weak slab. In this study, two 1:2 reduced scale SRC column-RC slab joint specimens are designed and fabricated for horizontal cyclic loading tests based on side slab-column joints of an auxiliary plant of a nuclear power plant. In order to ensure the ease of construction and stability of the connection between the reinforcement and the section steel, one structure (SR-2) with steel sleeves welded to the section steel and connected to the reinforcement in the joint area and the other structure (SR-1) with a stiffened steel plate (SSP) in the connection area on the basis of SR-2 were fabricated and tested in order to investigate the structural strengthening the joint. Based on the test results, the damage modes, hysteresis performance, energy dissipation capacity and stiffness degradation of the specimens were studied. A finite element analysis (FEA) model was developed and verified with the experimental results. The verified FEA model was used for parametrical study on effects of thickness, outer dimensions of SSP, a longitudinal reinforcement ratio in the RC slab and an axial pressure ratio. The test results show that the damage mode of specimens is shear failure at the RC slab and the damage of the SRC column is minor, which is in line with the design concept of the strong column and weak slab. The parametric study shows that increasing the thickness and outer size of SSP can improve the load-bearing capacity and initial stiffness of joints.